Association between TGF-β1 Polymorphisms and Head and Neck Cancer Risk: A Meta-Analysis - Shi, Quan; Wang, Xing; Cai, Chuan; Yang, Shuo; Huo, Na; Liu, Hongchen (Frontiers in Genetics, 2017)
Background and Objective: Despite that some studies have been conducted to explore the association between the single nucleotide polymorphisms (SNPs) in transforming growth factor beta 1 (TGF-β1) and head and neck cancer (HNC) susceptibility, the findings are still inconclusive. Therefore, we conduct this meta-analysis to quantitatively assess the association. Methods: Embase and PubMed were searched for all eligible clinical studies. The odds ratio (OR) and 95% confidence interval (CI) of each study were pooled to estimate the association between SNPs in the TGF-β1 and the HNC risk. Subgroup analyses were performed to explore whether particular characteristics were related to the value of overall ORs and 95% CIs. Results: Seven case-control studies, including three SNPs (-509C/T, 869T/C and 915G/C), were examined. Overall, this meta-analysis failed to identify a significant association between TGF-β1-509C/T, 915G/C polymorphism and HNC risk in any models. As for the 869T/C polymorphism, significant associations were observed in allelic model (C vs T: OR=1.351, 95%CI: 1.030-1.772), homozygote model (CC vs TT: OR=1.585, 95%CI: 1.026-2.449) and dominant model (CT/CC vs TT: OR=1.398, 95%CI: 1.008-1.937), as well as in the Asians (C vs T: OR=1.400, 95%CI: 1.003-1.956, CC vs TT: OR=1.814, 95%CI: 1.018-3.233). Conclusion: This meta-analysis failed to show statistical associations between TGF-β1 -509C/T, 915G/C polymorphism and HNC risk in any genetic models, but we find that TGF-β1 869C/T polymorphism may be involved in the susceptibility to HNC, especially in Asian patients. However, given the limitations of this meta-analysis, more well-designed studies are required in the future.